Cutaneous melanoma in France in 2015 attributable to solar ultraviolet radiation and the use of sunbeds. (18th May 2018) - Arnold, M.; Kvaskoff, M.; Thuret, A.; Guénel, P.; Bray, F.; Soerjomataram, I.
Abstract: Background: Exposure to solar ultraviolet radiation (UVR) and the use of UV‐emitting tanning devices are associated with cutaneous malignant melanoma occurrence. Objective: The aim of this study was to quantify the proportion and number of melanoma cases attributable to solar UVR exposure and sunbed use in France in 2015. Methods: Population attributable fractions (PAFs) and numbers of melanoma cases attributable to solar UVR exposure were estimated by age and sex using the incidence rates of a 1903 birth cohort as the primary reference. Further analyses were performed using the following: (i) contemporary melanoma incidence rates in low‐incidence regions within France and (ii) national melanoma incidence rates for the year 1980, as additional references. Assuming a 15‐year lag period, PAF and melanoma cases attributable to sunbed use were calculated using prevalence estimates from a cross‐sectional population survey and published relative risk estimates. Results: In 2015, an estimated 10 340 melanoma cases diagnosed in French adults were attributable to solar UVR exposure, corresponding to 83% of all melanomas and 3% of all cancer cases in that year. PAFs for melanoma were highest in the youngest age group (30–49 years) and higher in men than in women (89% vs. 79%). A total of 382 melanoma cases occurring in French adults in 2015 were attributed to the use of sunbeds, equivalent to 1.5% and 4.6% of all melanoma cases in men and women, respectively. Conclusions: A considerable proportion of melanoma cases in France in 2015 were attributable to solar UVR exposure, suggesting that targeted prevention strategies need to be implemented.